Communication and advertising in NGDOs: present and future - San Miguel, Aránzazu Román (IROCAMM - International Review Of Communication And Marketing Mix, 2019)
Non-Governmental Organizations for Development (NGDOs), as part of the Third Sector, coexist in society with large business conglomerates, trade unions, public entities, etc. that use communication to improve their bottom line, whether tangible or not. New technologies and the Internet are becoming indispensable tools to reach audiences, increasingly influenced by social networks, work, blogs, and so on. At a time when solidarity is more necessary than ever and administrative support is diminishing, NGDOs need to communicate what they do and how they do it, because their survival and that of those they assist is at stake. This paper seeks to highlight the lack of communicators in NGDOs throughout their existence. It shows that today most NGDOs still do not have expert communication officers, but they do have digitally trained people in their ranks in order to make themselves known and attract the attention of their target audiences. It seems that in the not too distant future communication will become a fundamental pillar for social entities.